Problem posing ability among prospective mathematics teachers - Rafi, Ibnu; Sugiman, Sugiman (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2019)
Posing mathematics problem is perceived as one of the learning strategies to promote students' skills in mathematics problem-solving as well as one of the crucial competencies that should be mastered by prospective mathematics teachers. Some people argued that for prospective mathematics teachers, posing mathematics problem itself is as important as solving mathematics problem because when they become mathematics teachers, there exist necessity for them to pose mathematics problem as a means for assessing students' understanding or achievement. The aim of this article, therefore, was to focus on the investigation into the prospective mathematics teachers' ability in posing mathematics problems. Relevant literature from several electronic databases such as SpringerLink, ScienceDirect, ResearchGate, and Google Scholar was searched based on the following keywords: "˜pre-service mathematics teacher', "˜problem-posing', "˜prospective mathematics teacher problem-posing', and "˜posing mathematics problem'. There was a total of 16 articles which were included into this review according to the determined inclusion criteria as follow: an empirical study that was published in journal or conference proceeding with the publication date from years of 2009 to 2019, written in English, full text, and discussing about prospective mathematics teachers' ability in posing problem-related to mathematics. There were as many as three themes that deal with the prospective mathematics teachers' ability to pose the mathematics problem, i.e. type of posed problem, ability in posing mathematics problem, and the difficulty which was experienced by prospective mathematics teachers in posing mathematics problem. These three themes and their implications are discussed in this article. Kemampuan calon guru matematika dalam mengajukan masalah Abstrak Pengajuan masalah matematika dapat dianggap sebagai salah satu strategi pembelajaran untuk mengembangkan keterampilan siswa dalam memecahkan masalah matematika serta sebagai salah satu kompetensi yang penting yang seharusnya dikuasai oleh calon guru matematika. Beberapa orang berpendapat bahwa untuk calon guru matematika, mengajukan masalah matematika itu sama pentingnya dengan memecahkan masalah matematika karena ketika mereka menjadi guru matematika, ada suatu keharusan bagi mereka untuk mengajukan masalah matematika sebagai saran untuk menilai pemahaman atau pencapaian siswa. Tujuan artikel ini, oleh karena itu, adalah untuk fokus pada penyelidikan kemampuan calon guru matematika dalam mengajukan masalah matematika. Literatur yang relevan dari beberapa basis data elektronik seperti SpringerLink, ScienceDirect, ResearchGate, dan Google Scholar dicari berdasarkan kata kunci berikut: "˜pre-service mathematics teacher', "˜problem-posing', "˜prospective mathematics teacher problem-posing', dan "˜posing mathematics problem'. Ada total 16 artikel yang dimasukkan ke dalam tinjauan ini sesuai dengan kriteria inklusi yang ditentukan sebagai berikut: studi empiris yang diterbitkan dalam jurnal atau prosiding seminar dengan tanggal publikasi dari tahun 2009 hingga 2019, ditulis dalam bahasa Inggris, teks lengkap, dan membahas tentang kemampuan calon guru matematika dalam mengajukan masalah yang berkaitan dengan matematika. Ada tiga tema yang berhubungan dengan kemampuan calon guru matematika untuk mengajukan masalah matematika, yaitu jenis masalah yang diajukan, kemampuan dalam mengajukan masalah matematika, dan kesulitan yang dialami oleh calon guru matematika dalam mengajukan masalah matematika. Ketiga tema dan implikasinya dibahas dalam artikel ini.